2021
DOI: 10.1002/jbt.22967
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cisplatin resistance by neferine/isoliensinine and their combinatorial regimens with cisplatin‐induced apoptosis in cisplatin‐resistant colon cancer stem cells (CSCs)

Abstract: Cisplatin chemotherapy to the colorectal cancer cells (CRCs) is accompanied by dose‐limiting adverse effects along with the acquisition of drug resistance implicating low therapeutic outcomes. The present study is aimed to evaluate the chemosensitizing efficacy of neferine/isoliensinine or combinatorial regimen of neferine/isoliensinine with cisplatin against CSCs (cisplatin resistant colon stem cells). CSCs were developed using pulse exposure of cisplatin to parental HCT‐15 cells. Neferine/isoliensinine or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Studies have shown that neferine cooperates with anticancer compounds (such as doxorubicin, paclitaxel, cisplatin, and vincristine) in many cancer cells, thus improving efficacy and combating chemotherapy resistance. Neferine combined with isoliensinine could downregulate the cell survival protein expression (PI3K/pAkt/mTOR) and activate mitochondria-mediated apoptosis by upregulating Bax, cytochrome c, caspase-3, and PARP cleavage expression while downregulating BCl-2 expression in cisplatin-resistant colon stem cells (CSCs) [ 171 ]. In addition, neferine can enhance the sensitivity of some types of cancer cells to chemotherapeutic drugs and reduce epithelial–mesenchymal transitions (EMT) due to chemoresistance against liver cancer cells.…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…Studies have shown that neferine cooperates with anticancer compounds (such as doxorubicin, paclitaxel, cisplatin, and vincristine) in many cancer cells, thus improving efficacy and combating chemotherapy resistance. Neferine combined with isoliensinine could downregulate the cell survival protein expression (PI3K/pAkt/mTOR) and activate mitochondria-mediated apoptosis by upregulating Bax, cytochrome c, caspase-3, and PARP cleavage expression while downregulating BCl-2 expression in cisplatin-resistant colon stem cells (CSCs) [ 171 ]. In addition, neferine can enhance the sensitivity of some types of cancer cells to chemotherapeutic drugs and reduce epithelial–mesenchymal transitions (EMT) due to chemoresistance against liver cancer cells.…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…At present, the molecular mechanism underlying cisplatin resistance are complex, including the inactivation of apoptosis, the reduction in the intracellular accumulation of the platinum, and the activation of epithelial-mesenchymal transition [4]. Many studies have shown that the cisplatin-resistant cancer cells have the lower levels of cisplatin-induced apoptosis than cisplatin-sensitive cells [33][34][35]. Liu signi cantly increased the apoptotic levels of LOVO cells, but in LOVO/DDP cells, this effect was not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Neferine, isoliensinine, and cisplatin exhibited a stronger cytotoxic activity against CSCs, with IC50 values of 6.5 μmol/L for neferine, 12.5 μmol/L for isoliensinine, and 120 μmol/L for cisplatin. Isoliensinine can induce the generation of ROS and block the sub G0 phase cell cycle, alleviate the expression of ERCC1, and decrease the cell survival protein expression (PI3K/pAKT/mTOR) and BCl-2, upregulating the expression of Bax, cytochrome c, caspase 3, and PARP cleavage, thereby activating mitochondria-mediated apoptosis in CSCs [ 247 ]. Moreover, ursolic acid inhibited tumor growth in nude mice transplanted with ovarian cancer stem cells in a dose-dependent manner, decreased the expression of ABCG2, promoted the apoptosis of CSCs, and improved the ability of cisplatin-induced apoptosis [ 248 ].…”
Section: Potential Mechanisms Of Plant-derived Natural Products In Th...mentioning
confidence: 99%